2020
DOI: 10.1182/blood.2019003336
|View full text |Cite
|
Sign up to set email alerts
|

Activation and suppression of hematopoietic integrins in hemostasis and immunity

Abstract: Nolte and Margadant review the current understanding of the activation and inactivation of integrin receptors expressed by hematopoietic cells and the role of these conformational changes in modulating platelet and leukocyte function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…Integrins are essential for hemostasis and immunity, because they regulate platelet aggregation, leukocyte adhesion and migration, and transforming growth factor-β activation [ 34 , 35 ]. In addition, it is becoming clear that integrins also control vesicular trafficking in platelets and leukocytes at several levels.…”
Section: Integrin Adhesion Complexes Regulate Platelet and Leukocyte mentioning
confidence: 99%
See 1 more Smart Citation
“…Integrins are essential for hemostasis and immunity, because they regulate platelet aggregation, leukocyte adhesion and migration, and transforming growth factor-β activation [ 34 , 35 ]. In addition, it is becoming clear that integrins also control vesicular trafficking in platelets and leukocytes at several levels.…”
Section: Integrin Adhesion Complexes Regulate Platelet and Leukocyte mentioning
confidence: 99%
“…Integrin cytoplasmic tails can induce profound differences in the behavior of distinct integrins, even when they bind the same ligand [ 64 ], which is most likely due to differences in the relative affinities for specific proteins. The cytotail of αvβ5 contains an insert of eight amino acids, as compared with integrin β1 or β3 tails [ 34 ], and may have an exceptionally high affinity for clathrin adaptors. Consistent with this idea is the observation that swapping the β5 tail with that of β1 or β3 induces a redistribution to FAs [ 59 ].…”
Section: Integrin Crosstalk With the Endocytic Machinery Regulates Admentioning
confidence: 99%
“…Using human leukocyte cell lines, this latter study then knocked down LCP1 and found that L-plastin depleted leukocytes were more adhesive, compared to controls, under conditions of flow. Taken together, these independent findings place L-plastin as a novel cytoplasmic suppressor of hematopoietic integrin adhesion operating through and ‘inside-out’ signaling mechanism (Nolte and Margadant 2020).…”
Section: Discussionmentioning
confidence: 90%
“…Recently, accumulating evidence demonstrates that ITGs are emerging as important regulators of immune cell signaling. [ 14 , 15 ] Thus, it is important to identify which subunits of ITG correlated with poor prognosis were mainly involved in the immune mechanism of LUAD. By analyzing the expression level of three ITGs of 3-ITG in immune cells associated with the recognition of tumor, it was found that only ITGAL had a strong correlation with a correlation coefficient (Cor) >0.5 and P < 0.05 ( Figure 7A–C ).…”
Section: Resultsmentioning
confidence: 99%